Artemisia annua L. polysaccharide improves the growth performance and intestinal barrier function of broilers challenged with Escherichia coli - Guo, Shiwei; Shi, Binlin; Xing, Yuanyuan; Xu, Yuanqing; Jin, Xiao; Hong, Lei; Zhang, Shengnan; Qiao, Min; Yan, Sumei (Frontiers in Microbiology, 2024)
With the high intensification of poultry breeding, a series of diseases caused by pathogenic bacteria threaten the health of poultry and human. Among them, poultry diseases induced by Escherichia coli cause significant economic loss every year. The aim of this study was to investigate the effects of dietary supplementation with Artemisia annua L. polysaccharide (AAP) on the growth performance and intestinal barrier function of broilers with Escherichia coli (E. coli) challenge. A total of 256 one-day-old chicks were randomly assigned to four treatment groups: control group (fed basal diet), AAP group (fed basal diet supplemented with AAP), E. coli group (fed basal diet and orally administered E. coli), AAP + E. coli group (fed basal diet supplemented with AAP and orally administered E. coli). Dietary AAP supplementation elevated the BW, ADG and ADFI in non-challenged broilers. AAP also increased the apparent metabolic rate of EE and Ca in E. coli-challenged broilers. Moreover, AAP not only enhanced the serum IgA content but also decreased the serum and jejunum content of IL-6, as well as the jejunum level of IL-1β in non-challenged broilers. AAP also down-regulates the mRNA level of inflammatory factors (IL-1β, IL-6, and TNF-α) by inhibiting the mRNA expression of TLR4 and MyD88 in intestinal NF-κB signaling pathway of E. coli-challenged broilers. Meanwhile, AAP up-regulates the activity and mRNA level CAT by down-regulating the mRNA level of Keap1 in intestinal Nrf2 signaling pathway of E. coli-challenged broilers, and decreased serum MDA concentration. AAP significantly elevated the mRNA level of CAT, SOD and Nrf2 in jejunal of non-challenged broilers. Interestingly, AAP can improve intestinal physical barrier by down-regulating serum ET content, increasing the jejunal villus height/crypt depth (VH/CD) and ZO-1 mRNA level in broilers challenged by E. coli. AAP also elevated the VH/CD and the mRNA level of Occludin, ZO-1, Mucin-2 in non-challenged broilers. Importantly, AAP reshaped the balance of jejunum microbiota in E. coli-challenged broilers by altering α diversity and community composition. In summary, AAP ameliorated the loss of growth performance in broilers challenged with E. coli, probably by regulating the intestinal permeability and mucosa morphology, immune function, antioxidant ability, and microbiota.